MAKNA PUBLIC RELATIONS DI OZ RADIO BANDUNG - Yusuf Yuliardi; Sri Dewi Setiawati (Lembaga Penelitian & Pengabdian Masyarakat Universitas Bina Sarana Informatika, 2014)
Abstract - The purpose of this study is to analyze the meaning of Public relations at OZ Radio 103.1 FM Bandung. There are three categories according to the theory of Public relations as a Communications Facilitator , Public relations as a Problem Solving Facilitator and Public relations as a Communications Technician . This study, classified into fenomenology research that seeks to develop theory. The Aims, are to find the meaning of public relations at OZ Radio 103.1 FM Bandung, and compare it with the theory used. The Approachment using descriptive research is research that aims to explain social systems, event or social relationships. This study characterized among other data collected and compiled initially described and analyzed the significance of public relations OZ Radio 103.1 Fm Bandung .The results showed, that the meaning of public relations at OZ Radio 103.1 FM Bandung is still aligned with the marketing department. So the PR division OZ Radio 103.1 FM Bandung is not a dominant coalition and not in the organization structure to act as a management function .The Conclusion research , Public relations OZ Radio 103.1 FM Bandung has an important role for the company, because it served as a Communication Facilitator , Problem Solving Process Facilitator and Communications Technician .Suggestions are, Public relations OZ Radio 103.1 FM Bandung undue straight down and sell the products of their clients , due to sales of the product should be taken over by marketing . Because the main task of public relations is as image building , while the main task of marketing is selling products . Keywords: Management of Public Relations, Public Relations, Radio Abstrak - Tujuan penelitian ini adalah untuk menganalisa makna Public relations di OZ Radio 103.1 FM Bandung dalam 3 kategori yang dijabarkan menurut teori yaitu Public relations sebagai Communications Facilitator, Public relations sebagai Problem Solving Facilitator dan Public relations sebagai Communications Technician. Penelitian ini diklasifikasikan ke dalam penelitian kualitatif deskriptif yang berusaha untuk mengembangkan teori. Bertujuan mengetahui makna public relations di OZ Radio 103.1 FM Bandung dan membandingkannya dengan teori yang digunakan. Metode yang digunakan adalah fenomenologi, dimana penelitian yang bertujuan mencari makna sebenarnya dari kedudukan seorang public relations. Penelitian ini memiliki ciri antara lain data yang dikumpulkan mula-mula disusun dan dijelaskan kemudian dianalisis mengenai makna public relations OZ Radio 103.1 Fm Bandung . Hasil penelitian menunjukkan bahwa makna public relations di OZ Radio 103.1 FM Bandung masih disejajarkan dengan marketing department. Sehingga divisi PR OZ Radio 103.1 FM Bandung tidak menjadi koalisi dominan dan tidak duduk dileher struktur organisasi untuk bertindak sebagai fungsi manajemen. Kesimpulan penelitan, Public relation OZ Radio 103.1 FM Bandung mempunyai peran penting bagi perusahaan karena telah berperan sebagai Communication Facilitator, Problem Solving Process Facilitator serta Communications Technician. Saran Public relations OZ Radio 103.1 FM Bandung tidak semestinya turun langsung dan menjual produk dari kliennya, karena untuk penjualan produk seharusnya diambil alih oleh marketing. Karena tugas utama seorang public relations adalah sebagai building image, sedangkan tugas utama marketing adalah selling product. Kata Kunci: Management Public Relations, Public Relations, Radio